Extraordinary Measures: The Role of Debt Levels in Fiscal Policy Responses to Covid-19 - Adam Elbourne; Giulia Piccillo; Konstantinos Velentzas (Center for Economic Studies and ifo Institute (CESifo), 2023)
We use SVAR models for 18 economies to estimate how much fiscal policy deviated from pre-pandemic norms during the Covid-19 pandemic. For most countries, fiscal policy was more expansive than the pre-pandemic norm predicts based on the state of the economy during the pandemic. The size of the deviation from the pre-pandemic norm is not related to the level of government debt on the eve of the pandemic, as fiscal space concepts would predict.
Keywords: E60; H50; C50; 330; Covid-19; fiscal policy; SVAR; fiscal space